Applied ethics in a digital world - Vasiliu-Feltes, Ingrid, 1971-; Thomason, Jane, 1958- (Advances in human and social aspects of technology book series., 2022)
"This book highlights core dilemmas we are facing as a society in the digital era, reviews key domains that need to be addressed in designing and deploying proactive ethical and data governance programs, and offers potential areas for further research"--